Lithium-Directed Transformation of Amorphous Iridium (Oxy)hydroxides To Produce Active Water Oxidation Catalysts - Esquius, Jonathan Ruiz; Morgan, David J.; Siller, Gerardo Algara; Gianolio, Diego; Aramini, Matteo; Lahn, Leopold; Kasian, Olga; Kondrat, Simon A.; Schloegl, Robert; Hutchings, Graham J.; Arrigo, Rosa; Freakley, Simon J. (Journal of the American Chemical Society, 2022)
The oxygen evolution reaction (OER) is crucial to future energy systems based on water electrolysis. Iridium oxides are promising catalysts due to their resistance to corrosion under acidic and oxidizing conditions. Highly active iridium (oxy)hydroxides prepared using alkali metal bases transform into low activity rutile IrO2 at elevated temperatures (>350 °C) during catalyst/electrode preparation. Depending on the residual amount of alkali metals, we now show that this transformation can result in either rutile IrO2 or nano-crystalline Li-intercalated IrOx. While the transition to rutile results in poor activity, the Li-intercalated IrOx has comparative activity and improved stability when compared to the highly active amorphous material despite being treated at 500 °C. This highly active nanocrystalline form of lithium iridate could be more resistant to industrial procedures to produce PEM membranes and provide a route to stabilize the high populations of redox active sites of amorphous iridium (oxy)hydroxides.
CRIS-Team Scopus Importer:2023-03-29